Open surgical embolectomy for cardiogenic cerebral embolism: Technical note and its advantages. (July 2021) - Matano, Fumihiro; Tamaki, Tomonori; Yamazaki, Michio; Enomono, Hiroyuki; Mizunari, Takayuki; Tateyama, Kojiro; Murai, Yasuo; Tanikawa, Rokuya; Morita, Akio
Highlights: Endovascular thrombectomy for cardiogenic cerebral embolism often fails to achieve recanalization. The advantages of surgical embolectomy are 1) high recanalization rate. The advantages of surgical embolectomy are 2) low rate of thrombus distal migration. The advantages of surgical embolectomy are 3) low rate of hemorrhagic complication. The advantages of surgical embolectomy are 4) short procedure time. Abstract: Background and importance: In cardiogenic cerebral embolism, early recanalization is the most important factor for good prognosis. However, endovascular thrombectomy often fails to achieve recanalization. We present an open surgical embolectomy technique and discuss its advantages. Clinical presentation: A 79-year-old woman developed right hemiparesis and severe aphasia. Magnetic resonance imaging revealed an acute cerebral infarction caused by left middle cerebral artery (MCA) occlusion. We attempted endovascular thrombectomy but failed because it was impossible to guide the catheter to the occlusion site. Hence, we converted to open surgical embolectomy. Sylvian fissure was widely opened. After confirming the range of thrombosis using indocyanine green videoangiography (ICGVAG), the proximal and distal arteries were secured, and a temporary clip was placed on the distal M2 to prevent distal thrombosis migration. MCA was cut approximately 3 mm from the bifurcation, and thrombosis was removed using micro-forceps. The proximal clip was simultaneously inserted but was not clamped because the thrombus was extruded by proximal vascular flow. Immediately after removing the thrombus, intense bleeding occurred from the proximal flow. An assistant clamped the proximal artery using the prepared clip, and the incised area of MCA was sutured using 9-0 threads. We finally confirmed blood flow after recanalization using ICGVAG. The time from skin incision to recanalization was 27 min. After the procedure, the patient developed slight aphasia but had no hemiparesis and was later transferred to a rehabilitation hospital. Conclusion: Open surgical embolectomy may be a secondary rescue treatment option in the case of endovascular thrombectomy failure.